Association of combination antiretroviral therapy with risk of neurological diseases in patients with HIV/AIDS in Taiwan: a nested case-control study - Chou, Chen-Hsing; Chiou, Jian-Shiun; Ho, Mao-Wang; Tien, Ni; Li, Te-Mao; Chiu, Mu-Lin; Tsai, Fuu-Jen; Wu, Yang-Chang; Chou, I-Ching; Lu, Hsing-Fang; Lin, Ting-Hsu; Liao, Chiu-Chu; et al. (Frontiers in Pharmacology, 2023)
Heterogeneous neurocognitive impairment remains an important issue, even in the era of combination antiretroviral therapy (cART), with an incidence ranging from 15% to 65%. Although ART drugs with higher penetration scores to the central nervous system (CNS) show better HIV replication control in the CNS, the association between CNS penetration effectiveness (CPE) scores and neurocognitive impairment remains inconclusive. To explore whether ART exposure is associated with the risk of neurological diseases among patients with HIV/AIDS, this study in Taiwan involved 2,571 patients with neurological diseases and 10,284 matched, randomly selected patients without neurological diseases between 2010 and 2017. A conditional logistic regression model was used in this study. The parameters for ART exposure included ART usage, the timing of exposure, cumulative defined daily dose (DDD), adherence, and cumulative CPE score. Incident cases of neurological diseases, including CNS infections, cognitive disorders, vasculopathy, and peripheral neuropathy, were obtained from the National Health Insurance Research Database in Taiwan. Odds ratios (ORs) for the risk of neurological diseases was conducted using a multivariate conditional logistic regression model. Patients with a history of past exposure (OR:1.68, 95% confidence interval [CI]:1.22–2.32), low cumulative DDDs (< 2500) (OR:1.28, 95% CI:1.15–1.42), low adherence (0 < adherence (ADH) ≤ 0.8) (OR:1.46, 95% CI:1.30–1.64), or high cumulative CPE scores (> 14) (OR:1.34, 95% CI:1.14–1.57) had a high risk of neurological diseases. When stratified by classes of ART drugs, patients with low cumulative DDDs or low adherence had a high risk of neurological diseases, including NRTIs, PIs, NNRTIs, INSTIs, and multi-drug tablets. Subgroup analyses also suggested that patients with low cumulative DDDs or low adherence had a high risk of neurological diseases when they had high cumulative CPE scores. Patients with high cumulative DDDs or medication adherence were protected against neurological diseases only when they had low cumulative CPE scores (≤ 14). Patients may be at risk for neurological diseases when they have low cumulative DDDs, low adherence, or usage with high cumulative CPE scores. Continuous usage and low cumulative CPE scores of ART drugs may benefit neurocognitive health in patients with HIV/AIDS.